Sociolinguistic variation and language acquisition across the lifespan - Ghimenton, Anna; Nardy, Aurélie; Chevrot, Jean-Pierre (Studies in language variation, 2021)
"This volume provides a broad view of the field of sociolinguistic variation in acquisition. Favored by the current scientific context where interdisciplinarity is particularly encouraged, the chapters bring to light the complementarity between the social and cognitive sciences approaches to language acquisition. The book integrates sociolinguistic and psycholinguistic issues by bringing together scholars who have been developing conceptions of language acquisition throughout the lifespan that take into account the language-internal or cross-linguistic variation in first and second language, as well as in first and second dialect acquisition contexts. The volume gathers theoretical and empirical research and provides an excellent basis for scholars and students wanting to delve into the social and cognitive dimensions of both production and perception of sociolinguistic variation. The book enables the reader to understand, on the one hand, how variation is acquired in childhood or at a later stage and, on the other hand, how perception and production feed into one another building awareness of the social meaning underpinning language variation"--